Serum protein binding and the antimicrobial activities of garcinia kola, kola acuminata and kola nitida seed extracts on the agents of respiratory tract infections (2009)
The kinetics of bactericidal activity of the methanolic extracts of powdered seeds of Garcinia kola (Heckel), Kola acuminata and Kola nitida obtained by soxhlet extraction, were studied using two bacterial sensitive strains of Staphylococcus aureus and Pseudomonas aeruginosa. The study showed that the three extracts at the concentrations used against the two test organisms, Staphylococcus aureus OOUTH206 (0.5mg/ml for Garcinia kola, 4mg/ml for Kola acuminata and Kola nitida) and Pseudomonas aeruginosa UCH189 (8mg/ml for Garcinia kola, 15mg/mi for Kola acuminata and Kola nitida); had activity on the two microorganisms. There was a gradual reduction in the number of viable microbial counts as evident in the reduction in the cell number at the different time intervals. Similar procedure was carried out in the presence of 5% serum protein and it was observed that the activities of the various extracts were altered significantly indicating the effect of serum protein binding on the Constituents of Garcinia kola, Kola acuminata and Kola nitida seed extracts. The results were expressed in percentage viable count of the inoculum size and showed that the percentage viable count decreases with time in varying degrees. The reduction was more intense with G. kola extract than the other extracts on S. aureus as well as on P. aeruginosa towards the third and fourth hours. The effect of serum protein was seen to affect the activities of all the extracts in varying degrees as shown in the graphs plotted.